The Traditional Chinese Architecture And Feng Shui Application In Low Ti Kok Mansion, Kajang, Selangor - Chong, Kai Zhen (2017)
This thesis focuses on the traditional Chinese architecture and feng shui. The Chinese shophouses and mansions in Malaysia were built based on the Chinese architecture with traces of European and Malays architectural elements in the design. Feng shui is one of the oldest traditional Chinese practices especially on the architectural theory and also famous a popular life principles. Basically, the Thoughts School of feng shui consists of two schools; the Form School and the Compass School, which are important practices in the architectural theory. The problem statement of this study was a lack of knowledge on the Chinese mansions in the term of traditional Chinese architecture and feng shui, and how feng shui had influenced the building and design of Chinese mansions.